2019
DOI: 10.1186/s12877-019-1229-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in the association between frailty and dietary consumption in Japanese older people: a cross-sectional study

Abstract: Background Female sex is an important factor predisposing individuals to frailty. Appropriate nutrition is one of the most effective ways to prevent older adults from developing frailty; Sex-related differences have also been detected in the association between nutritional intervention and health-related outcomes. However, few studies have discussed these sex-related differences. The aim of the present study was to investigate the sex-related differences in the association between frailty and diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
7
15
0
2
Order By: Relevance
“…Our preliminary study underlined the fact that as many as about one-half of the older adults living in nursing homes were frail, and 38.5% were still prefrail; moreover, frailty tended to be more prevalent in women than men. A number of studies [ 27 29 ] from different countries (i.e., Japan, Southern Italy) were consistent with our results, which demonstrated that frailty was highly prevalent, and the prevalence of frailty in women was higher than in men. A greater understanding of the reasons and implications of this physical phenotype across sex was required.…”
Section: Discussionsupporting
confidence: 91%
“…Our preliminary study underlined the fact that as many as about one-half of the older adults living in nursing homes were frail, and 38.5% were still prefrail; moreover, frailty tended to be more prevalent in women than men. A number of studies [ 27 29 ] from different countries (i.e., Japan, Southern Italy) were consistent with our results, which demonstrated that frailty was highly prevalent, and the prevalence of frailty in women was higher than in men. A greater understanding of the reasons and implications of this physical phenotype across sex was required.…”
Section: Discussionsupporting
confidence: 91%
“…Our preliminary study underlined the fact that as high as about one-half of the older adults living in nursing homes were frail, and 38.5% were still prefrail; moreover, women were frailer than men. Many studies [24][25][26] from different countries (i.e., Japan, South Italy) are consistent with our results, which demonstrated that frailty was highly prevalent, and the prevalence of frailty in women was higher than in men. A greater understanding of the reasons and implications of this physical phenotype across sex is required.…”
Section: Discussionsupporting
confidence: 92%
“…Gender was identi ed as a risk factor for predicting the older adults' frailty [14,27]. This study's ndings agree on previous studies in reporting that female older adults in low-income countries, South Asia in particular, are generally reluctant about their health complexities and they do not take proper initiatives for health check-ups [27,[54][55][56]. A considerable inconsistency in the research outcomes is that the female older adults who live without a partner are more inclined to medical conditions [57][58][59].…”
Section: Discussionsupporting
confidence: 84%